2015
DOI: 10.1007/s40865-015-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

When Is a Youth’s Debt to Society Paid? Examining the Long-Term Consequences of Juvenile Incarceration for Adult Functioning

Abstract: Purpose To examine the long-term consequences of juvenile incarceration on functioning in adulthood (ages 27–33). Methods Propensity score analysis was used to compare incarcerated youth with those who were never incarcerated in a subsample of individuals who had experienced at least one police contact in adolescence. Data were drawn from the Seattle Social Development Project (SSDP), a multiethnic, gender balanced community sample. Results Youth who were incarcerated in adolescence were more likely to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 53 publications
(65 reference statements)
0
43
0
Order By: Relevance
“…The delinquency measure was derived from a series of questions concerning minor acts of delinquency such as drawing graffiti or stealing items worth less than $5; moderate acts including property destruction or theft of items worth up to $50; or severe acts such as selling drugs, using a weapon to get something, or breaking and entering. In line with previous investigations seeking to capture both the chronicity and severity of adolescent delinquency, items were weighted by severity: 1 for minor acts, 2 for moderate acts, and 3 for severe acts (Gilman et al 2015). Substance use was measured by self-reports of alcohol, tobacco, and marijuana use in the past month.…”
Section: Methodsmentioning
confidence: 99%
“…The delinquency measure was derived from a series of questions concerning minor acts of delinquency such as drawing graffiti or stealing items worth less than $5; moderate acts including property destruction or theft of items worth up to $50; or severe acts such as selling drugs, using a weapon to get something, or breaking and entering. In line with previous investigations seeking to capture both the chronicity and severity of adolescent delinquency, items were weighted by severity: 1 for minor acts, 2 for moderate acts, and 3 for severe acts (Gilman et al 2015). Substance use was measured by self-reports of alcohol, tobacco, and marijuana use in the past month.…”
Section: Methodsmentioning
confidence: 99%
“…In future research, for instance, inclusion of a comparison group characterized by a vulnerable background but without having experienced institutionalization, would help shed light on the extent to which institutionalization significantly contributes to poorer adult outcomes (e.g. [22]). …”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that, compared to the controls, previously institutionalized men and women showed worse outcomes with regard to psychosocial functioning, a measure that included living conditions, work, marriage, psychopathology, and crime. Using propensity score matching, Gilman et al [22] studied the long-term consequences of juvenile incarceration on functioning in adulthood. Their findings indicate that youths who were institutionalized in adolescence were more likely to have alcohol abuse problems and to receive public assistance between ages 27 and 33 compared to youths who did not experience institutionalization.…”
Section: Adult Outcomes Of Vulnerable Youthsmentioning
confidence: 99%
“…Criminology research reinforces this(Gilman, Hill, and David Hawkins, 2015; Green, Palmquist, and Schickler, 2006;Rade, Desmarais, and Burnette, 2018).…”
mentioning
confidence: 73%